IMPLEMENTATION MODEL INDONESIAN HEALTHY FAMILY APPROACH PROGRAM POLICY (PIS-PK): CASE STUDY IN NORTH GORONTALO REGENCY - Youke Lidya Herty Lumataw; Asna Aneta; Rauf A. Hatu; Yanti Aneta (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Implementation policy public is stages important thing that determines success achievement objective policy . This study to study various implementation models such as Edward III, CFIR, SAF, as well top-down and bottom-up approaches , to understand factors determinant success policies , especially in context sector health based on family . Research show that factor key in implementation covering clarity communication , readiness source power , attitude implementer , and structure responsive bureaucracy . In addition that , involvement stakeholders interest local and adaptation to context socio-political become determinant effectiveness implementation policy.Analysis This confirm importance multi-level and collaborative approach in implementation policy . With merge various theoretical models and empirical data , results study This can become reference strategic For strengthening policy more public​ effective and sustainable .